Energijska učinkovitost enostanovanjskih bioklimatskih stavb glede na podnebne spremembe - Pajek, Luka (visokošolska dela, 2022)
In light of the current climate change, efforts to recognise and mitigate its impact on the energy performance of buildings are increasing. However, there is still a lot to learn about the impact of global warming on the built environment. Despite numerous research studies, the impacts of global warming on the bioclimatic potential and the applicability of passive design measures in the case of single-family buildings are not completely clear. The exposed knowledge gaps were filled in the doctoral dissertation by performing an extensive literature review and numerous simulations. An essential part of the research refers to the presented method of calculating the location’s bioclimatic potential, where the existing methodology was upgraded by considering the data on solar radiation. Moreover, the research results represent an essential contribution, as they showed the need for a conceptual leap in the current bioclimatic design practice of single-family buildings. The data obtained by 15,897,600 parametric simulations represent essential information for timely adaptation to climate change. It was found that, given the combined energy need for heating and cooling, the energy efficiency of single-family buildings in the future depends on the location. It can be generally expected that energy efficiency will be lower in warm climates, higher in cold and firstly higher and then lower in temperate climates. Based on the data, a new approach to bioclimatic building design was proposed, where passive design measures are applied to ensure energy efficiency in the current and future climate while the future overheating vulnerability is addressed.
Keywords: bioclimatic design; bioclimatic potential; bioklimatski potencial; bioklimatsko načrtovanje; built environment; civil engineering; climate change; Disertacije; doctoral thesis; efficient energy use; Energijska učinkovitost; gradbeništvo; grajeno okolje; Klimatske spremembe; low-energy buildings; nizkoenergijske stavbe; pasivni ukrepi; passive measures; podnebne spremembe; residential buildings; stanovanjske stavbe; učinkovita raba energije; Zgradbe